Does folic acid reduce congenital anomalies and adverse pregnancy outcomes in women received long-term low dose methotrexate? - Farag, Ahmed M.; Ibrahim, Safaa A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Methotrexate (MTX) which is folic acid antagonist is used to treat many diseases, including rheumatic, inflammatory, autoimmune disorders or malignancies; it is also used for the medical treatment of ectopic pregnancy and termination of pregnancy. The objective of this study was to assess the impact of folic acid in preventing congenital anomalies (CAs) in the fetus of pregnant that take long-term low dose methotrexate. Methods: The study included 1569 with history of low dose methotrexate therapy <25 mg/week that stopped one month before pregnancy, they were divided into 3 groups; Group 1 comprised 272 pregnant women, Group 2 comprised 367 pregnant women both groups take folic acid 4-5 weeks preconception and for the first 12-13 weeks gestation, the dose in the 1st group was 0.4 mg/day while in 2nd Group 4 mg/day, Group 3 comprised of 930 pregnant disease-matched with no folic acid. Group 4 comprised of 1015 pregnant no underlying autoimmune and no folic acid intake. Results: The overall rate of CAs and cardiovascular CAs were higher in fetuses of Group 3 (OR: 1.7; 95% CI: 1.1-2.7) and (OR: 2.7; 95% CI: 1.4-5.2) respectively compared to the overall rate of CAs and cardiovascular CAs in other groups. Other adverse outcomes as abortion, preterm delivery, preeclampsia, placenta abruption, PROM, low birth weight, admission to NICU, IUGR and IUFD were higher in Group 3 and 4 than in Group 1 and 2. There were no significant differences in umbilical arterial PH. The Apgar scores <7 at 1, 5 min and gestational age at delivery were higher in Group 1 and 2 than Group 3 and 4. Conclusions: There was a certain reduction in methotrexate teratogenic effect on the fetuses with folic acid intake during pregnancy, these pregnancies might benefit from taking of folic acid in high doses before conception and during the first trimester of pregnancy and improvement in fetal and maternal outcomes but the explanation of this effect requires further study.